Technical and environmental characterization of hydraulic and alkaline binders. (20th September 2018) - Espuelas, S.; Echeverria, A.M.; Marcelino, S.; Prieto, E.; Seco, A.
Abstract: Portland cement is a widely used binder in construction and building applications because of its good properties. Despite its convenience as construction material, the social demands and policies trends are requesting a lower impact and more sustainable cement manufacturing industry. The most effective ways to reach this goal are the substitution of clinker by different wastes or by-products in the cement composition or the development of more sustainable binders like the alkali activated binders. This work analyzes from a technical and environmental point of view the substitution of a clinker based CEM I common cement for the construction mortars manufacturing. Four common cements with different ground granulated blastfurnace slags (GGBS) or fly ashes (FA) contents as well as fifteen alkali activated binders (AAB) combinations were considered. Fresh consistency, density, compressive strength (CS) tests and life cycle analysis were carried out to state the ability of these different hydraulic and alkaline activated binders for the CEM I substitution. The results obtained demonstrated the technical and environmental convenience of these binders for the construction mortars manufacturing. Highlights: Hydraulic mortars reached longer starting setting times than the alkaline ones. Setting periods were similar for the hydraulic and for the alkaline mortars. Hydraulic binders required more water added than the alkaline ones. GGBS allows the high strength alkali activated binders manufacturing. GGBS and FA decrease the impact related to the binders manufacturing.